Maximum paste coating thickness without voids clogging of pervious concrete and its relationship to the rheological properties of cement paste. (20th April 2018) - Xie, Xiaogeng; Zhang, Tongsheng; Yang, Yongmin; Lin, Ziyu; Wei, Jiangxiong; Yu, Qijun
Graphical abstract: To evaluate the maximum paste coating thickness on aggregate (MPCT) that will not result in clogging of voids, a paste drainage test on flow table was developed, and test variables in terms of the number of flow table drops, the sieve mesh size and the aggregate size were optimized, such that the paste coating thickness measured in the test provided an estimate of the MPCT. Furthermore, uniform relationships between yield stress, viscosity, mini-slump spread and MPCT were established, which will give a better understanding of a critical criterion for mixture design and clogging prediction of pervious concrete. Highlights: Maximum paste coating thickness (MPCT) on aggregate without clogging of voids was defined. A paste drainage test was developed on a flow table to determine the MPCT. Test variables (the number of flow table drops, sieve size, and aggregate size) were optimized. Uniform relationships between yield stress, viscosity, mini-slump spread and MPCT were established. The reliability of relationships was validated by comparing predicted and measured MPCTs. Abstract: All mixture design methods for pervious concrete have been proposed under the hypothesis that cement paste uniformly coats on the surface of aggregate and does not drain off from the aggregate surface to clog the interconnected voids between aggregate particles. To evaluate the maximum paste coating thickness on aggregate (MPCT) that will not result in clogging of voids, understanding of the relationship between the MPCT and the rheological properties of cement paste was reviewed and theoretically analyzed in the present study. A paste drainage test was developed on a flow table to determine the MPCT, with specification of test variables (in terms of the number of flow table drops, the sieve mesh size, and the aggregate size) to ensure good repeatability and precision. Based on testing data of 39 cement pastes, uniform relationships between yield stress, viscosity, mini-slump spread and MPCT were established. The resulting empirical functions were validated by comparing the predicted and measured MPCTs for additional tests. The results will give a better understanding of a critical criterion for mixture design and clogging prediction of pervious concrete.